Implementation of Health Service Policy for Social Security Administrator Agency Participants in the Technical Implementation Unit of Bawomataluo Community Health Center, Fanayama District, South Nias Regency - Syukur Duha; Tunggul Sihombing; Asima Yanty S Siahaan (International Journal of Scientific Multidisciplinary Research, 2024)
Health services are one of the crucial aspects in the health development of a country. The Indonesian government has implemented the National Health Insurance Program (JKN) through the Social Security Administering Body (BPJS) to provide equal access to health services to all Indonesian citizens. One of the focal points of health services is the Regional Technical Implementation Unit (UPTD) of the Bawomataluo Health Center, Fanayama District, South Nias Regency. This study aims to examine the implementation of the BPJS participant health service policy at the UPTD Bawomataluo Health Center. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation studies. The research informants consisted of health workers, UPTD administrators, and BPJS participants. The results of the study showed that the implementation of the health service policy for BPJS participants at the UPTD Bawomataluo Health Center faced several challenges, such as limited human resources and health facilities, as well as administrative constraints and information on BPJS health services. However, efforts to improve the quality of services continue to be carried out through training for health workers, improving facilities, and socializing to the community